Pharmacokinetic-pharmacodynamic modeling of daurisoline and dauricine in beagle dogs - Shi Shao-Jun; Chen Hui; Gu Shi-Fen; Zeng Fan-Dian (Acta Pharmacologica Sinica, 2016)
AIM: To study the combined pharmacokinetic-pharmacodynamic (PK-PD) model of daurisoline and dauricine, and compare their effects on cardiac electrophsiology, blood pressure, and hemodynamics in beagle dogs. METHODS: The plasma drug concentration was determined by the reversed-phase HPLC method and the effects on cardiac and hemodynamics were recorded by polygraph. The pharmacokinetic and PK-PD model parameters were calculated. RESULTS: The pharmacokinetics were best fitted to a two-compartment open model, and the relationship between effect and effect compartment concentration of both drugs could be represented by the sigmoid-E(max) model. There were no significant differences in main pharmacokinetics and PK-PD parameters between the two drugs. CONCLUSION: No statistically different kinetic disposition characteristics and potencies of inhibitory effects on myocardial function of daurisoline and dauricine were found in beagle dogs.